Analisis Pengendalian Risiko Terhadap Peningkatan Kinerja Pekerjaan Konstruksi (Studi Kasus Asrama Haji Gorontalo) - Evan Kusuma Wijaya; Edhi Wahjuni Setyowati; Yulvi Zaika (Rekayasa Sipil, 2017)
A good construction management can support the acceleration of the infrastructure construction and a low performance in implementation of the construction projects will lead to delay and cost overrun. This paper is intended to identify the risk factors which affect to performance of construction project. Gorontalo Hajj Dormitory construction project are not completed within the estimated scheduled and cost. Data in this research were collected through questionnaires from stakeholders. Regression model of an analysis result then simulated with Monte Carlo method and the variables in this model are the most dominant risk factor which influence on a performance. The most dominant risk for cost and schedule performance is bad condition during construction, incorrect of implementation methods, rework and equipment failure. The cost and schedule performance of the construction work are in poor condition. Generated statistical model is aligned with Earn Value Method and can be apply on the field.